Improving the Principles of Identifying Critical Requirements for the Assembly of High-Precision Products - A. V. Nazaryev; P. Yu. Bochkarev (Advanced Engineering Research)
Introduction. The problem of improving the manufacturing of high-precision products is currently becoming a key one, since the requirements for them are constantly being tightened. Maintaining assembly quality and accuracy is an important aspect of manufacturing precision products. Standard approaches to this process do not always have sufficient versatility. Existing studies that aim to develop universal approaches, such as end-to-end production design or the application of parallel engineering principles, also have a number of shortcomings. These include the fact that the given approaches do not fully take into account information about the technology capabilities of a particular production when making design decisions, and do not consider the relationship between the manufacturing preparation of machining and mechanical assembly industries. That is why studies aimed at developing such universal approaches have high applicability. To solve these problems, the authors conceptually developed a set of formalized design procedures for a system of accounting requirements for the assembly of high-precision products in the design of machining processes. However, to effectively identify the numerous requirements for the assembly of high-precision products (output parameters) and select those that cannot be provided by the method of complete interchangeability (critical elements), additional research is needed. The research objective is to develop principles for identifying the output parameters of high-precision products and detecting critical elements. To achieve this goal, it is required to solve the following problems: to formulate principles for constructing generalized surface graphs of high-precision products; to develop standards for classifying output parameters and identifying critical ones.Materials and Methods. To conduct the research, a high-precision assembly unit was selected — “Stator Package 2”. The research was carried out under real conditions of the existing multiproduct manufacture. For this assembly, a generalized surface graph was constructed, including information about the nature and sequence of surfaces, requirements for the assembly, dimensional tolerances and tolerances of shape and location, with its subsequent analysis.Results. This paper presents the results of research on improving the enlarged block of design procedures for analyzing requirements for the assembly of high-precision products of the designed system. The paper established the relationship between the accuracy of dimensional tolerances and the tolerances of the shape and location of the surfaces of the product to which these dimensions belonged. Based on the relationship obtained, an order was determined for the unambiguous identification of critical elements.Discussion and Conclusion. The application of this technique makes it possible to increase the reliability of the source information obtained during the implementation of an enlarged block of design procedures, as well as the validity and efficiency of identifying rational manufacturing technologies at subsequent stages of the system implementation, while providing the specified quality, accuracy of products, and reducing the complexity and cost of their manufacture.